Atrial Cardiomyopathy: An Unexplored Limb of Virchow's Triad for AF Stroke Prophylaxis - Darlington, Ashley; McCauley, Mark D. (Frontiers in Cardiovascular Medicine, 2020)
The most dreaded complication of atrial fibrillation is stroke, and 70-80% of patients with AF-related stroke die or become disabled. The mechanisms of thromboembolism in AF are multifactorial, with evidence demonstrating that all three criteria of Virchow’s triad are satisfied in AF: abnormal stasis of blood, endothelial damage, and hypercoagulability. Mechanistic insights into the latter two limbs have resulted in effective stroke prophylactic therapies (left atrial appendage occlusion and oral anticoagulants); however, despite these advances, there remains an excess of stroke in the AF population that may be due, in part, to a lack of mechanistic understanding of atrial hypocontractility resulting in abnormal stasis of blood within the atrium. These observations support the emerging concept of atrial cardiomyopathy as a cause of stroke. In this Review, we evaluate molecular, translational, and clinical evidence for atrial cardiomyopathy as a cause for stroke from AF, and present a rationale for further investigation of this largely unaddressed limb of Virchow’s triad in AF.